Growing CeO2 Nanoparticles Within the Nano-Porous Architecture of the SiO2 Aerogel - Caddeo, Francesco; Loche, Danilo; Casula, Maria F.; Corrias, Anna (Frontiers in Chemistry, 2020)
In this study, new CeO2-SiO2 aerogel nanocomposites obtained by controlled growth of CeO2 nanoparticles within the highly porous matrix of a SiO2 aerogel are presented. The nanocomposites have been synthesized via a sol-gel route, employing cerium (III) nitrate as the CeO2 precursor and selected capping agents to control the growth of the CeO2 nanoparticles, which occurs during the supercritical drying of the aerogels. Samples with different loading of the CeO2 dispersed phase, ranging from 5 to 15%, were obtained. The nanocomposites showed the morphological features typical of the SiO2 aerogels such as open mesoporosity with surface area values up to 430 m 2 ·g -1 . TEM and XRD characterizations show that nanocrystals of the dispersed CeO2 nanophase grow within the aerogel already during the supercritical drying process, with particle sizes in the range of 3 to 5 nm. TEM in particular shows that the CeO2 nanoparticles are well distributed within the aerogel matrix. We also demonstrate the stability of the nanocomposites under high temperature conditions, performing thermal treatments in air at 450 and 900 °C. Interestingly, the CeO2 nanoparticles undergo a very limited crystal growth, with sizes up to only 7 nm in the case of the sample subjected to a 900 °C treatment.